Compressive responses and strengthening mechanisms of aluminum composite foams reinforced with graphene nanosheets. (November 2019) - Li, Weiting; Yang, Xudong; He, Chunnian; Sha, Junwei; Shi, Chunsheng; Li, Jiajun; Zhao, Naiqin
Abstract: The controllable design of composition and structure makes incorporating reinforcements to be a promising way to fabricate aluminum (Al) composite foams. In this work, graphene nanosheets (GNSs) decorated with copper (Cu) nanoparticles reinforced Al composite foams are successfully synthesized via shift-speed ball-milling and space-holder method. The compressive properties and energy absorption capacity of composite foams increase first and then decrease with the increase of the GNSs@Cu content. Unexpectedly, the introduction of the GNSs@Cu has not changed the ductile failure mode of pure Al foams. The strengthening mechanisms of composite foams include load transfer strengthening and dispersion strengthening, and the toughening mechanism of composite foams is considered as crack bridging. The 0.75 wt% GNSs@Cu/Al composite foams possess the optimal yield stress (24.7 MPa), plateau stress (41.3 MPa) and energy absorption capacity (22.8 MJ/m 3 ), which has an improvement of 104.7%, 113.7% and 115.1% in comparison with that of pure Al foams. Graphical abstract: Image 1